Performance Enhancement in Cellular Network Using Decoding-based Successive Interference Cancellation Technique - & Wilson Nwankwo, Kingsley Eghonghon Ukhurebor (Covenant Journal of Physical and Life Sciences, 2019)
Interference if not properly attended to could have negative influence on the air interface performance of any wireless network service. Hence, there is a need to moderate interference in cellular network system. This study is aimed at analysing the performance of decoding-based successive interference cancellation technique. The was done analysing the performance of decoding based successive interference cancellation on uplink High Speed Uplink Packet Access Enhanced Dedicated Physical Data Channel. From the analysis, simulations and results obtained from this study, we have been able to show that this technique would reduce the load of the cell and increase the network capacity of the cellular network provider, thereby improving the quality of service.